Intellectual property rights over ethnic communities' knowledge (2002)
Knowledge accumulated for centuries by ethnic communities about their habitat is increasingly being used for commercial purposes in fields such as pharmacy and agriculture. Transnational corporations and research laboratories use knowledge obtained from the analysis of plants and other biological samples provided by ethnic communities, or from the observation of their traditional practices. This paper proposes an interpretation of intercultural processes that take place in the exchange of traditional knowledge between ethnic groups and different kinds of agents in modern societies. The exchange between indigenous communities that possess the knowledge and researchers from universities and transnational corporations willing to develop and exploit that knowledge is marked by a deep information asymmetry. Guidelines for a regulatory framework protecting vernacular knowledge and simultaneously providing incentives for modern scientific research are suggested. Under this scheme, communities might improve their ability to defend their rights and demand the enforcement of certain rules conditioning the use of traditional knowledge by firms, laboratories, and research institutes. At the same time, investment for research in this field would be stimulated.